Intellectual disability in higher education: self-perceived training needs of university teachers - Corbí, Miguel (2022)
Given that only initial steps in the PSE of the students with ID have been taken in Europe, the objective of this research was to determine formative needs of the university teachers in the selected European countries with different tradition and practices of inclusive education. The sample was composed of 1009 university teachers. The instrument consisted of a questionnaire ad hoc on perceptions about the importance of different aspects of education for people with intellectual disability, and about the educational skills self-competence perception. We used a quasi-experimental cross-sectional design to administer the questionnaires by controlling as many strange variables as possible. To this end, an action protocol was developed that included solutions to the most common problems.